Analisis Keterampilan Proses Sains Peserta Didik Madrasah Ibtidaiyah pada Masa Pandemi Covid-19 - Arwan Wiratman; Bayu Widiyanto; Moh. Fadli (Bidayatuna, 2021)
This study aims to determine the application and results of the analysis of science process skills (KPS) of students during the covid-19 pandemic in online learning activities. To collect data, researchers used questionnaires, interviews and documentation methods. In this study, the researcher used an instrument consisting of a statement with 4 (four) answers provided by the researcher, for example SS (strongly agree) with a score of 4 (four), S (agree) with a score of 3 (three), TS (disagree with ) with a score of 2 (two), and STS (strongly disagree) with a score of 1 (one). The number for each variable is 10 statements and answered by 14 students, so the minimum score for one statement item is 14 and the highest score is 56. This research was carried out on students of class V MI Manggarupi academic year 2020/2021 in the even semester totaling 14 (fourteen) people. Based on the results of data analysis, it can be seen that during the Covid-19 pandemic, science process skills (KPS) were well received by students and the results of the analysis of Science Process Skills (KPS) obtained seemed successful and had a positive impact on students.